2002
DOI: 10.1021/cm011241o
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Titanyl Phthalocyanine Films Grown by Directional Crystallization on Oriented Poly(Tetrafluoroethylene) Substrate

Abstract: Highly oriented films of titanyl phthalocyanine (TiOPc) were obtained by high-vacuum sublimation onto an oriented poly(tetrafluoroethylene) (PTFE) substrate. The dependence of the structure and morphology on deposition parameters (substrate temperature T s, deposition time t, and deposition rate τ) was followed by X-ray diffraction, transmission electron microscopy (TEM), and atomic force microscopy (AFM) to uncover the origin of the oriented growth process. At T s = 100 °C, an original growth mechanism was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
90
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 40 publications
11
90
1
Order By: Relevance
“…More complicated XRD peaks appeared at 150°C, in which the diffraction peaks at 7.5°, 12.5°, 25.3°, and 28.6°were assigned to a-phase and the diffraction peak at 26.2°was belonged to b-phase. [18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…More complicated XRD peaks appeared at 150°C, in which the diffraction peaks at 7.5°, 12.5°, 25.3°, and 28.6°were assigned to a-phase and the diffraction peak at 26.2°was belonged to b-phase. [18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films.…”
supporting
confidence: 79%
“…[18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films. A highly ordered a-TiOPc film with an "edgeon" molecular orientation was selectively grown on the surfaces of the gold substrate modified with a self-assembled monolayer of octadecanethiol.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…[21][22][23] However, a more detailed analysis of the literature data shows that the LC films studied previously were not in the Col h phase. For example, the films of TiOPc [21] or HBC-C8,2 [23] were in the crystalline state whereas the films of HBC-PhC12 were in the LC state but in a mesophase different from Col h (Col r phase at room temperature [24] ). Similar studies have been conducted on Ada-PBT that was in the glassy state produced by quenching from hexagonal columnar plastic or hexagonal columnar ordered phases.…”
mentioning
confidence: 89%